The Relationship between Stock Return and Trading Volume in Malaysian ACE Market - Tapa, Afiruddin; Hussin, Maziah (International Journal of Economics and Financial Issues, 2016)
The relationship between stock return and trading volume in Malaysian ACE market has been analysed in this study. There are two objectives of conducting the analysis; (1) to investigate the relationship between stock return and trading volume in Malaysian ACE market, and; (2) to conclude whether the relationship of trading volume and stock return on Malaysian ACE market is consistent with the weak-form of the efficient market hypothesis. The empirical result proves a significant positive contemporaneous relationship between stock return and trading volume. Thus, the first objective is satisfied. Second objective is proven that Malaysian ACE market is contradicted with the weak-form of efficient market hypothesis. Keywords: stock return, trading volume, Malaysian ACE market JEL Classifications: G1, G12